Reversal of Aluminium chloride induced neurobehavioral deficit by Selenium: Involving NLRP3 inflammasome and cholinergic innervation: Neuroprotective Effect of Selenium through NLRP3 Pathway - Tembhurne, Sachin; Deo, Atharva; Gavade, Shubham; Chaudhary, Somdatta; Garud, Aniket (Iranian Journal of Pharmaceutical Sciences, 2025)
This study examines the efficacy of selenium as a therapeutic agent for reversing neurobehavioral deficits. A docking analysis was conducted to elucidate the interaction between selenium and the NLRP3 inflammasome residue. The research involved synthesizing and validating selenium nanoparticles within a controlled experimental design that employed Aluminium chloride (AlCl3) to induce neurotoxicity, followed by comprehensive neurobehavioral evaluations in Wistar rats. The results revealed that a one-month oral selenium administration led to significant enhancements in cognitive and motor functions, reduced proinflammatory cytokine levels, and decreased β-amyloid aggregation within the brain. Quantitative findings demonstrated that selenium treatment led to a marked enhancement in locomotor activity (from 54.83±0.60 to 60.5±0.76 counts, p<0.0001), improved performance within the radial arm maze (with baited arm entries rising from 9.83±0.58 to 16.5±0.43, p<0.0001). They augmented the recognition index in the novel object recognition assessment (from 33.77±0.74% to 61.38±1.10%, p<0.0001). On a biochemical level, selenium was found to decrease malondialdehyde concentrations and elevate antioxidant enzyme levels (SOD, CAT, GSH, p<0.01) while also significantly reducing levels of β-amyloid and TNF-α in the brain tissue. Additionally, selenium exhibited neuroprotective properties through both antioxidant mechanisms and cholinesterase pathways, thereby establishing it as a promising candidate for treating neurobehavioral deficits and neuroinflammation.